2014
DOI: 10.2478/pjvs-2014-0096
|View full text |Cite
|
Sign up to set email alerts
|

Trueperella pyogenes and Escherichia coli as an etiological factor of endometritis in cows and the susceptibility of these bacteria to selected antibiotics

Abstract: The aim of this study was to determine the percentage of participation of particular species of microorganisms, isolated from the uterus of cows with endometritis and from cows without inflammatory lesions of the uterus, in the same postpartum period. The aim of the study was also to examine how long after parturition non-treated endometritis persists. Moreover, antibiotic susceptibility tests were carried out of the bacterial isolates dominating in the uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
1
21
0
5
Order By: Relevance
“…Brodzki et al [ 22 ] found that E. coli isolated from bovine uteri was sensitive to amoxicillin-clavulanic acid by the percentage of 100% supporting the results of high sensitivity to this antibiotic. On the contrary, Li-ming et al [ 23 ] found that E. coli was highly resistant to amoxicillin.…”
Section: Discussionmentioning
confidence: 89%
“…Brodzki et al [ 22 ] found that E. coli isolated from bovine uteri was sensitive to amoxicillin-clavulanic acid by the percentage of 100% supporting the results of high sensitivity to this antibiotic. On the contrary, Li-ming et al [ 23 ] found that E. coli was highly resistant to amoxicillin.…”
Section: Discussionmentioning
confidence: 89%
“…One pure culture of T. pyogenes partially matched the NGS results since the number of reads was lower (11.28%) than those of the most abundant genus, Fusobacterium (74.04%). T. pyogenes cooperates with environmental anaerobes, such as Fusobacterium necrophorum , to produce infections, such as endometritis in cows, and increases the possibility of uterine inflammatory conditions while intensifying disease symptoms [ 54 56 ]. Fusobacterium is known to cause sporadic bovine abortion [ 57 , 58 ], but the impact of mixed infections on abortions has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli and other Gram-negative bacteria are the major pathogens associated with endometritis (Janowski et al, 2013;Sens and Heuwieser, 2013;Brodzki et al, 2014;Wagener et al, 2014). Lipopolysaccharides (LPSs) are the major structural components of the cell wall of Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%